2015
DOI: 10.12963/csd.15247
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Gestures in Toddlers with Developmental Language Delay and Their Relations to Language Development

Abstract: Objectives: Using communicative gestures are one of the related factors of language development in toddler periods. The purpose of this study was to examine communicative gestures in toddlers with and without developmental language delay (DLD) and their relations to language development. Methods: The participants were 10 toddlers with DLD, 10 typically developing chronological age-matched toddlers (CA-matched group), and 10 typically developing language age-matched toddlers (LA-matched group). Communicative ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…1.2.1 | Gesture use in South Korea Only a handful of studies have examined gesture use in Korean children, often over a wide range of ages (e.g., Kim & Kim, 2006;Lee & Kim, 2013;Lee & Lee, 2015), mostly focusing on overall frequencies of gesture use. For example, Kim and Kim (2006) examined gesture use between 7-and 24-month during a structured play time with an experimenter and found that the number of gestures produced increased with children's ages.…”
Section: Introductionmentioning
confidence: 99%
“…1.2.1 | Gesture use in South Korea Only a handful of studies have examined gesture use in Korean children, often over a wide range of ages (e.g., Kim & Kim, 2006;Lee & Kim, 2013;Lee & Lee, 2015), mostly focusing on overall frequencies of gesture use. For example, Kim and Kim (2006) examined gesture use between 7-and 24-month during a structured play time with an experimenter and found that the number of gestures produced increased with children's ages.…”
Section: Introductionmentioning
confidence: 99%
“…https://doi.org/10.12963/csd.19623 264 http://www.e-csd.org YoonKyoung Lee, et (Paul et al, 1991). 보통 말늦은 영유아의 주된 판별기준이 되어 온 표현어휘수나 낱말조합 여부보다 먼저 발달하는 것으로 알려진 수 용언어 (Carson, Klee, Perry, Muskina, & Donaghy, 1998), 의사소 통적 몸짓 사용과 이해 (Lee & Lee, 2015;Thal, Tobias, & Morrison, 1991), 의도적 의사소통행동 (Rescorla & Merrin, 1998), 음절 내에 서의 자음 사용이나 자음 목록과 같은 말소리 발달 (Carson et al, 1998;Mirak & Rescorla, 1998;Paul & Jennings, 1992), 상징발달 (Rescorla & Goossens, 1992 Hong & Kim, 2005;Thal & Tobias, 1992 Rescorla (2002Rescorla ( , 2005Rescorla ( , 2009는 24-31개월 사이에 있는 영유아를, Paul (1991)은 18-34개월, Thal, Oroz와 McCaw (1995 (Hong & Kim, 2005;Thal et al, 1991;Thal & Tobias, 1992 (Carson, Klee, Carson, & Hime, 2003;Mirak & Rescorla, 1998;Paul & Jennings, 1992) 홍경훈, 김영태(2005). 종단연구를 통한 '말늦은아동 (late-talker)'의 표현어휘발달 예측요인 분석.…”
unclassified
“…많은 선행연구들은 영아의 의사소통적 몸짓 사용 빈도가 이후의 언어발달을 예측해준다고 보고하였다 (Capirci et al, 1996;Iverson & Goldin-Meadow, 2005;Rowe & Goldin-Meadow, 2009 (Crais, Douglas, & Campbell, 2004;Harris, Barlow-Brown, & Chasin, 1995). Camaioni, Castelli, Longobardi와 Volterra (1991) (Chang, Choi, & Kim, 2005;Kim & Kim, 2006;Lee & Lee, 2015;Lee, Jeon, & Lee, 2014;Shin & Kim, 2016 Table 3). (Kim, Kim, Yoon, & Kim, 2003 (Butterworth & Morissette, 1996;Camaioni et al, 1991;Iverson & Goldin-Meadow, 2005;Özçalıskan & Goldin-Meadow, 2006…”
unclassified